Content Management System Sebagai Penguat Pelaku UMKM melalu Pelatihan Media Pemasaran Online - Iwan Purwanto; Adrian Sjamsul Qomar; Rully Mardjono; Anik Nur Habyba (Abdimas Universal, 2022)
This training activity has the aim of providing an understanding of technological developments and their use, as well as providing training on the process of designing a website based on website content processing management, so that it leads to digital-based marketing. The method used in this activity uses the OPAKK method where the activity emphasizes material development, application, and confirmation and ends with a brief consolidation. This training activity has been able to provide scientific enrichment to MSME actors, this is evidenced by the presence of 86.2% of participants who are very satisfied with the activities carried out and have a good impact scientifically and develop insight for participants and businesses in general.